LOCUTIONARY AND ILLOCUTIONARY ACTS FOUND IN INFOMALANG TWITTER ACCOUNT - KURNIA, DESI (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Speech act, locutionary act, illocutionary act, Internet, twitter, tweet, Infomalang.Language is always related to acts. When people are doing communication,they are not only delivering the message, but also performing an action from the utterance. Speech acts can be found in daily communication, for example in the Internet through social media, twitter. In this study, the researcher analyzes speech act within utterances found  in Infomalang twitter account. There are two problems to be solved: (1) What are the locutionary and illocutionary acts found in Infomalang twitter account? (2) What are the types of locutionary and illocutionary acts applied in Infomalang twitter account?This study used qualitative approach in document analysis since it focused onanalyzing the utterances written in infomalang twitter account. The data werecollected from April 5th 2014 to April 20th 2014 which were published on Saturdays and Sundays from 1 pm until 3 pm. Then the data were analyzed  to find out the types of locutionary acts by using Levinson’s theory and the types of illocutionary acts by using Searle’s theory.From 59 utterances, it was found that the most frequent type of illocutionaryacts found in Infomalang twitter account is declarative. This type is found 29utterances which are used to give information. The second type is interrogative which are used to ask question found 22 utterances. The last type is imperative which are to make someone do something found 7 utterances. While the types of illocutionary acts it was found that the most frequent type of illocutionary acts found in Infomalang twitter account is directive. There are 45 directives utterances, 11 representatives utterances, 1 commisive utterance, and 1 expressive utterance. The researcher did not find declaration.The researcher suggests that the next researchers analyze the perlocutionaryact of the utterances. In addition, it is recommended to analyze the same data by using other theories of pragmatics from other experts. The next researchers are also suggested to use another object in order to broaden the comprehension in speech acts such as movies, novels, and speeches.